PEMANFAATAN PLATFORM MERDEKA MENGAJAR SEBAGAI UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN - Endang Setiariny (Jurnal Lingkar Mutu Pendidikan, 2023)
This research is a descriptive quantitative research, which was conducted from April to September. The target population was Sekolah Penggerak Angkatan 1 (PAUD, SD, SLB, SMP and SMA levels) in East Jakarta and South Jakarta, DKI Jakarta province, with a total of 55 schools. One data sample was obtained for each school level per region (10 samples in total). The data collection technique was a questionnaire using a Likert scale collected through the “Daring system”. The aims and benefits of the research are: 1) As input for school principals in an effort to improve the quality of learning in their educational units so that they can improve the quality of education. 2) As input for school principals to motivate in a participatory manner in utilizing the Merdeka Mengajar Platform in their education units 3) As input for researchers and readers who care about education and want to support the achievement of national education goals. This can be done through utilization of the Merdeka Mengajar platform in an effort to improve the quality of learning.